Akuntansi Sumber Daya Manusia Sebuah Penilaian tentang Asset dan Modal Manusia - Anggarani, Dwi - (Jurnal Manajemen Akuntansi dan Bisnis, 2008)
Recently, the subject of human resources accounting still have a motion. In conceptual frame work develop through on capitalization of human resources expenditure. This capitalization of expenditure is only focus on matching cost an revenue principles an emphasize on historical perspective. While, human resources information should be provide the empowerment, motivation, and development of human resources. According to this statement, human resources information. The content of human resources accounting is financial information transactions, which is relate on those empowerment, motivation, and development human resources activities. Keywords: human resources accounting, Asset, capitalization of human resources.